Male sex and pretreatment weight loss are associated with poor outcome in patients with advanced non-small cell lung cancer treated with immunotherapy: a retrospective study - Jingxiao Jin; Jacqueline Visina; Timothy F. Burns; Brenda Diergaarde; Laura P. Stabile (Scientific Reports, 2023)
Abstract The influence of sex and body mass index (BMI) on the efficacy of immune checkpoint inhibitors (ICIs) in advanced non-small cell lung cancer (NSCLC) patients remains unclear. We conducted a retrospective study to evaluate the relationship between sex, BMI, pretreatment weight loss (PWL), and clinical outcomes in 399 stage IV NSCLC patients treated with ICIs using data abstracted from medical records. Multivariable Cox proportional hazards models were used to assess the impact on overall survival and progression-free survival. Females were significantly more likely to experience immune-related adverse events and had a significantly lower risk of death compared to males in our patient cohort. In stratified analyses, the latter was limited to those receiving first-line monotherapy. BMI was overall not significantly associated with outcome. However, underweight patients had a significantly higher risk of both progression and death compared to normal weight patients in the first-line monotherapy group. When stratified by sex, underweight males had a significantly higher risk of progression and death compared to normal weight males. This was not observed among females. Those with PWL had overall significantly worse outcomes compared to those without. In stratified analyses, PWL was associated with significantly worse OS in both females and males. Stratified by treatment, the worse outcome was limited to those receiving ICI monotherapy. In summary, utilizing real-world data, this study suggests that male sex, being underweight, and PWL negatively impact ICI efficacy in NSCLC patients. Therapeutic approaches to improve ICI outcomes in underweight patients and those with PWL should be investigated.